2000
DOI: 10.1152/jappl.2000.89.5.1868
|View full text |Cite
|
Sign up to set email alerts
|

Regional blood flow during exercise in humans measured by near-infrared spectroscopy and indocyanine green

Abstract: Using near-infrared spectroscopy (NIRS) and the tracer indocyanine green (ICG), we quantified blood flow in calf muscle and around the Achilles tendon during plantar flexion (1-9 W). For comparison, blood flow in calf muscle was determined by dye dilution in combination with magnetic resonance imaging measures of muscle volume, and, for the peritendon region, blood flow was measured by (133)Xe washout. From rest to a peak load of 9 W, NIRS-ICG blood flow in calf muscle increased from 2.4+/-0.2 to 74+/-5 ml x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 27 publications
3
115
0
1
Order By: Relevance
“…Following an intravenous dose of ICG, laser fluorescence videography is used to create a video image of dye uptake and clearance as an indicator of tissue perfusion. Boushel et al [40] reported that ICG video angiography determined dermal viability with high sensitivity and also had the advantage of being able to correlate structure (i.e. coagulated dermal vessels) with function (i.e.…”
Section: Vital Dyesmentioning
confidence: 99%
“…Following an intravenous dose of ICG, laser fluorescence videography is used to create a video image of dye uptake and clearance as an indicator of tissue perfusion. Boushel et al [40] reported that ICG video angiography determined dermal viability with high sensitivity and also had the advantage of being able to correlate structure (i.e. coagulated dermal vessels) with function (i.e.…”
Section: Vital Dyesmentioning
confidence: 99%
“…NIR spectroscopy (NIRS) oximetry is widely accepted to be reliable in the determination of oxy-hemoglobin (HbO 2 ), deoxy-hemoglobin (Hb), total hemoglobin concentration (THC), and blood oxygen saturation (StO 2 ) in deep tissues. 8,[26][27][28][29][30] Diffuse correlation spectroscopy (DCS) flowmetry is a more recent application of dynamic NIRS, which has been developed to examine relative blood flow (rBF) changes within deep tissue microvasculature. 6,22,31 DCS operates on the principle that photons injected into biological tissues diffuse and generate timevarying light speckle fluctuations due to the motion of moving scatterers in the tissue (e.g., red blood cells).…”
Section: Introductionmentioning
confidence: 99%
“…NIRS has been applied to measure the oxygenation and hemodynamics of a variety of tissues, including muscle, brain, and connective tissue. With an adequate optode separation (more than 20 mm), the skin and the subcutaneous fat constitutes less than 5% of the signal measured over a given body segment in lean subjects [1,2]. The NIRS signal therefore predominately reflects the microcirculation and O 2 availability of tissue, which is dependent on interoptode distance, 2-6 cm deep [1].…”
Section: Near Infrared Spectroscopy (Nirs) Is a Relatively Newmentioning
confidence: 99%
“…Nevertheless, most studies on muscle oxygenation and hemodynamics were performed on healthy adults and adult patients [1,4,7] and on term and preterm neonates [8,9]. In a recent study we analyzed FBF in children and adolescents with type I diabetes and healthy children and adolescents [6].…”
Section: Near Infrared Spectroscopy (Nirs) Is a Relatively Newmentioning
confidence: 99%
See 1 more Smart Citation